Influences of Maternal Conjugated Linoleic Acid and Essential Fatty Acid Supply During Late Pregnancy and Early Lactation on T and B Cell Subsets in Mesenteric Lymph Nodes and the Small Intestine of Neonatal Calves - Liermann, Wendy; Viergutz, Torsten; Uken, Katrin Lena; Vogel, Laura; Gnott, Martina; Dannenberger, Dirk; Tuchscherer, Armin; Kienberger, Hermine; Rychlik, Michael; Tröscher, Arnulf; Hammon, Harald Michael (Frontiers in Veterinary Science, 2020)
Conjugated linoleic acid (CLA) isomers are known for their health promoting effects in mammals and metabolic functions in dairy cows and are synthesized in the forestomach depending on essential fatty acid (EFA) intake. The current preliminary study investigated effects of a maternal fatty acid supplementation (MFAS) during late pregnancy and early lactation with coconut oil (CON, control), CLA (Lutalin®) or CLA+EFA (Lutalin®; linseed oil; safflower oil) on plasma fatty acid composition and T and B cell subsets in mesenteric lymph nodes (MLN) and the small intestine of 5 day-old calves. MFAS of CLA+EFA increased α-linolenic, eicosapentaenoic, docosapentaenoic and n-3 fatty acid proportions in calf plasma fat on day 1 and 5 after birth (P < 0.05). On day 5, CLA and CLA+EFA calves showed higher plasma fat trans-10, cis-12 CLA proportions and CLA calves had higher plasma cis-9, trans-11 CLA proportions compared to CON calves (P < 0.1). MFAS of CLA tended to increase CD4+ T cell subsets in MLN and increased CD21+ B cell subsets in ileal lamina propria compared to CON but decreased CD2+ T cell subsets in jejunal lamina propria (P < 0.05). CLA+EFA decreased CD4+ T cell subsets in MLN compared to CLA (P < 0.05). MFAS of CLA seemed to affect the intestinal adaptive immune system of calves but additional EFA supplementations reversed CLA effects. Possible direct CLA and EFA effects or whether changes in milk composition affected this immune modulation must be clarified in further studies.